Nongenetic engineering nanozyme proximity labeling reveals subcellular in situ interactomes and trafficking pathways of nanoparticles - Chao Jiang; Yiyang Fu; Baichuan Jin; Rongzi Gao; Wenwei Li; Ze Wang; Haozhe Huang; Zirui Zhuang; Yunlu Dai; Ji Jing; Yuan Liu (Proceedings of the National Academy of Sciences, 2026)
Elucidating the dynamic interactions between nanocarriers and cellular machinery is critical for advancing targeted nanomedicine. However, the optical microscopy imaging techniques can only provide a generalized view of nanomedicine localization. Proteomics approaches require cell lysis which disrupt native protein coronas during isolation, obscuring real-time intracellular trafficking mechanisms. Although proximity labeling enables in situ investigation of intracellular protein–protein interactions, it relies on genetically engineered enzyme fusion, thus limiting applicability across diverse systems. In this study, we report nanozyme proximity labeling (NPL), a genetic engineering-free strategy that harnesses the intrinsic peroxidase activity of Fe 3 O 4 nanoparticles (NPs) to biotinylate proximal proteins within live cells. NPL achieves rapid biotinylation of NP-interacting proteins during intracellular transit. Using streptavidin pulldown and LC–MS/MS, we mapped high-fidelity in situ interactomes and suggested distinct trafficking pathways for mitochondrial-targeted Fe 3 O 4 @TPP NPs and nontargeted Fe 3 O 4 NPs. Our NPL interrogates the native NP–protein corona–organelle interfaces, offering a generalizable platform to decipher subcellular targeting mechanisms and accelerate nanomedicine optimization.